The Potential of Phytochemicals Lycopene in Prevention of Bone Loss due to Decreased Estrogen Hormone in Humans and Experimental Animals - erdayanti, fansurina yuli; Atmaka, Dominikus Raditya; Kagawa, Masaharu (Universitas Airlangga, 2022)
Osteoporosis is a condition of decreased bone mass and disruption of bone microarchitecture that often occurs in the elderly. One of the causes of osteoporosis is menopause as reduced estrogen secretion increases bone resorption by osteoclasts activity, and the body's oxidative stress. Currently, osteoporosis is still a major cause of morbidity and mortality in the elderly. Prevention is vital in reducing this disease. Recent studies have shown a reduction in bone loss with lycopene consumption. High serum lycopene is also reported to be associated with decreased protein oxidation and bone resorption in postmenopausal women. This literature aimed to examine and analyze the research results related to the potential of lycopene on bone loss based on molecular and clinical research evidence in preventing osteoporosis in elderly women. Literature review on published papers in English in the last 10 years (2011 – 2021) was conducted using electronic database. Reviewed experimental and cohort studies on elderly women and experimental animals showed influence and effect of lycopene on bone loss. Lycopene may contribute in reduction of oxidative stress caused by reduced secretion of estrogen.